SISTEM INFORMASI MANAJEMEN SURAT PADA FITUR SURAT DINAS DI BADAN PUSAT STATISTIK KABUPATEN PRINGSEWU - Ridho Sholehurrohman; Igit Sabda Ilman; Mita Anggraaeni; rahman taufik; Muhaqiqin (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2025)
The development of information technology is getting faster so that there are many uses of computer-based programs that help the performance of an organization, both offices and companies. One of the organizations that utilizes information technology is the BPS Pringsewu. In data processing, BPS really determines how far the level of accuracy and precision of the statistical data produced. Also in its development, the BPS Pringsewu made use of the use of computer technology by using a mail management information system. In the mail management information system it is effectively and efficiently to assist the process of inputting data encountered and possibly when errors (fails) occur when typing is done repeatedly. From the results of the research conducted, it can be concluded that the Mail Management Information System on Official Letter Features is a website-based information system that has two levels of users, namely admin and employees. This system is expected to facilitate agencies in the process of storing incoming and outgoing mail data, and facilitate the process of automatically assigning outgoing mail numbers. Furthermore, from the results of black-box testing and User Acceptance Testing was found that this system has user friendly features making it easier for users to use the system, seen in the average test questionnaire getting 95.68%.